Tommy Tregennis - Phillips, Mary Elizabeth, 1857-1945; Wheelhouse, M. V. (Mary V.) (Salt Lake City, UT : Project Gutenberg, 2013)
"Tommy Tregennis" by Mary Elizabeth Phillips is a children's novel written in the early 20th century. The story revolves around a young boy named Tommy Tregennis as he navigates childhood adventures and familial dynamics in a quaint coastal village. Through familiar experiences and emotions, the book seeks to capture the innocence and imagination of childhood, emphasizing themes of family love, mischief, and the transition from boyhood. The opening of "Tommy Tregennis" introduces us to the titular character, a spirited five-year-old boy with a penchant for mischief. As Tommy comes home with torn trousers after playing near the sea, he grapples with the fear of disappointing his mother, Mammy, while simultaneously navigating the joys and challenges of childhood. Tommy's inner thoughts and interactions with his family, particularly his mother, set the tone for the narrative, which is rich in charm and humor. As he contemplates his school day and the expectations of growing up, readers are drawn into Tommy's world, where every day is filled with potential for adventure and lessons to be learned. (This is an automatically generated summary.)
Release date is 2013-05-29
E-text prepared by Juliet Sutherland, Matthew Wheaton, and the Online Distributed Proofreading Team
Keywords: Boys -- Fiction; Cornwall (England : County) -- Fiction; Families -- Fiction